Preparation method and application of perovskite thin film
By using amidinourea phosphate as an additive in perovskite solar cells, the problem of insufficient stability of perovskite solar cells is solved, and higher photoelectric conversion efficiency and stability are achieved.
Patent Information
- Application Number
- CN202411727190.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Problems such as ion migration, thermal decomposition and phase transition of perovskite solar cells during environmental stimulation such as heat, humidity and light have led to insufficient stability, becoming a bottleneck for commercial applications.
Amidinourea phosphate is used as a perovskite additive and added to the perovskite precursor solution. Through the combined action of guanidine ions and phosphate groups, the surface defects of the perovskite film are passivated from multiple directions to form an intermediate complex to stabilize the perovskite crystal structure.
It significantly improves the photoelectric conversion efficiency and stability of perovskite solar cells and extends the retention time of the functional conversion efficiency of the device.
Smart Images

Figure CN119630248A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite solar cells, and in particular relates to a preparation method and application of a perovskite film. Background Art
[0002] With the increasing depletion of traditional fossil energy and the increasing demand for energy, finding a new type of renewable energy has become a new challenge facing human society. Solar energy is an important renewable energy source and has received more and more attention from researchers. At present, the most widely used way to utilize solar energy is to use the photovoltaic effect of semiconductor materials to prepare solar cell devices, thereby converting solar energy into electrical energy. Therefore, the development of new solar cells with high efficiency and low cost has become a necessary technical basis for realizing the application of solar photovoltaic power generation. As a representative of the third generation of thin-film batteries, perovskite solar cells have the advantages of high conversion efficiency, low cost, low pollution, and simple preparation process. Thanks to the excellent optoelectronic properties of perovskite materials, such as high absorption coefficient, adjustable band gap, high carrier mobility, long carrier lifetime and diffusion length, the functional conversion efficiency (PCE) of perovskite solar cells (PSCs) has increased significantly, soaring from 3.8% to 26.7%, as certified by NREL, showing broad application prospects. Although PSCs have experienced rapid development and PCE has been rapidly improved, the stability of PSCs is still considered a bottleneck for commercial standards due to various issues such as ion migration, thermal decomposition and phase transition of perovskite materials when exposed to environmental stimuli such as heat, humidity and light.
[0003] In the existing research history, a good way to improve the stability of PSCs is to add additives with specific structures to the perovskite precursor solution, and use the reaction between the additive and the perovskite material to passivate specific defects while adjusting the perovskite crystallization process, thereby improving the photoelectric conversion efficiency and device stability. Therefore, additives are crucial for achieving efficient and stable PSCs. At present, there are literatures using guanidine chloride as a perovskite additive, guanidine ion (GA + ) can passivate defects and improve the quality of perovskite films. In addition, a large number of molecules containing phosphate groups are also widely used in perovskite precursor solutions. Molecules containing phosphate can passivate grain boundary defects due to the regulation of perovskite film crystallization and the anchoring effect on uncoordinated cations, so that the improved device shows higher PCE and stronger stability.
[0004] However, both guanidine additives and phosphoric acid-containing molecules have only a single functional group, and are often a single optimization for perovskites. The range of passivation defects is quite limited, and the passivation effect of the entire device still needs to be improved. Summary of the invention
[0005] In response to the problems raised in the above background technology, the purpose of the present invention is to provide a method for preparing a perovskite film and its application, aiming to passivate the surface defects of the perovskite film from multiple directions, enhance the passivation effect of the perovskite solar cell, and improve the photoelectric conversion efficiency and stability of the perovskite solar cell.
[0006] In order to achieve the above technical effects, the technical solution of the present invention is implemented as follows:
[0007] In a first aspect, the present invention provides a method for preparing a perovskite film, which comprises the following steps:
[0008] Step 1, preparing a perovskite precursor solution;
[0009] Step 2, adding guanyl phosphate urea to the perovskite precursor solution of step 1 to obtain a modified perovskite precursor solution;
[0010] Step 3: Spin-coat the modified perovskite precursor solution in step 2 onto the substrate using a solution spin coating method to prepare a perovskite film.
[0011] Phosphate guanyl urea, also known as phosphate guanyl urea, has a molecular formula of C2H7N4O5P and a structural formula as shown in formula (I).
[0012]
[0013] As can be seen from the above structural formula, guanyl phosphate urea is rich in various groups: guanidine group, phosphate group, carbonyl group, etc. Therefore, the present invention adds guanyl phosphate urea to the perovskite precursor solution as a perovskite additive, and can make full use of the mechanism of guanidine ions and phosphoric acid molecules to passivate the defects of perovskite films. Guanidine ions and phosphoric acid molecules jointly strengthen the passivation of perovskite. More importantly, the present invention adds guanyl phosphate urea to the perovskite precursor solution as a perovskite additive. During the phase transition from liquid phase to solid phase, guanyl phosphate urea is combined with lead iodide to form an intermediate complex, which alleviates the aggregation speed of metal ions, thereby facilitating the dispersion of lead iodide, and providing a basis for the subsequent formation of uniform perovskite crystals. In addition, the intermediate complex formed by guanyl phosphate urea and lead iodide can be used as a crystal nucleus for the in-situ growth of perovskite, and the perovskite crystal structure is optimized by controlling the formation and growth of the nucleus to make it more uniform and stable.
[0014] In some embodiments of the present invention, the perovskite precursor solution is obtained by dissolving an ABX3 type perovskite material in an organic solvent, wherein A is at least one of Cs, MA, and FA, B is at least one of Pb and Rb, and X is at least one of Br and I.
[0015] Furthermore, the organic solvent is a mixed solvent of DMF and DMSO, the DMF is N,N-dimethylformamide, and the DMSO is dimethyl sulfoxide. More preferably, the volume ratio of DMF to DMSO in the organic solvent is 4:1. The organic solvent is a medium for dissolving perovskite precursor materials, and its specific functional groups have an important influence on the coordination between the solvent and the perovskite precursor. The polarity of the solvent determines its coordination ability, thereby affecting the nucleation and growth of perovskite crystals and the morphology of the deposited perovskite film. Therefore, by adjusting the characteristics of the solvent, the film formation kinetics and film quality of the solution-processed perovskite film can be effectively controlled.
[0016] In some embodiments of the present invention, the amount of guanyl phosphate urea added is 0.8-1.5 g per liter of perovskite precursor solution.
[0017] In some embodiments of the present invention, step 3 comprises:
[0018] Step 3.1, using a two-step solution spin coating method to spin coat the modified perovskite precursor liquid in step 2 onto a substrate to obtain a perovskite wet film, the process parameters of the two-step solution spin coating method are: the first step rotation speed is 1000 rpm, and the spin coating time is 10 s; the second step rotation speed is 3000 rpm, and the spin coating time is 40 s. The anti-solvent anisole is added dropwise 15 seconds before the spin coating; further, the amount of the anti-solvent anisole added is 10% of the volume of the organic solvent.
[0019] Step 3.2, annealing the perovskite wet film obtained in step 3.1 to obtain a perovskite thin film, wherein the process parameters of the annealing treatment are: annealing temperature 100° C., annealing time 10 min.
[0020] In a second aspect, the present invention provides the use of the perovskite film obtained by the above preparation method in a perovskite solar cell.
[0021] Furthermore, the structure of the perovskite solar cell includes a transparent electrode, a hole transport layer, a light absorption layer, an electron transport layer and a metal electrode stacked in sequence, and the light absorption layer includes the perovskite film obtained by the above preparation method.
[0022] In some embodiments of the present invention, the light absorption layer further includes an upper interface passivation layer disposed on the upper surface of the perovskite film and a lower interface passivation layer disposed on the lower surface, the passivation solution of the upper interface passivation layer is an IPA solution containing PEAI, the passivation solution of the lower interface passivation layer is an IPA solution containing Al2O3, the PEAI is phenylethylamine iodide, and the IPA solution is an isopropanol solution. By modifying the surface of the perovskite film to form a passivation layer with good stability, unnecessary surface reactions and composite behaviors can be prevented, losses can be effectively reduced, and the photoelectric conversion efficiency of the solar cell can be further improved.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention can passivate the surface defects of the perovskite film from multiple directions by adding guanidine phosphate urea as a perovskite additive to the perovskite precursor solution, including: (1) using -NH2 in guanidine to passivate the uncoordinated ion defects in the perovskite, gradually reducing non-radiative recombination and improving device performance; (2) passivating grain boundary defects by bifunctional phosphate groups, releasing residual strain, inducing grain enlargement and improving crystallinity; (3) P=O and C=O contained in the guanidine phosphate urea molecule can coordinate with Pb, and the molecule can also form hydrogen bonds with the perovskite, and P=O / C=O·…·H─N and FA + and O─H··I interactions, thereby stabilizing PbI6 4- Octahedron; (4) During the phase transition from liquid to solid, guanyl urea phosphate combines with lead iodide to form an intermediate complex, which slows down the aggregation rate of metal ions, thereby facilitating the dispersion of lead iodide and providing a basis for the subsequent formation of uniform perovskite crystals; (5) The intermediate complex formed by the combination of guanyl urea phosphate and lead iodide can serve as the nucleus for the in-situ growth of perovskite. By controlling the formation and growth of the nucleus, the perovskite crystal structure can be optimized to make it more uniform and stable.
[0025] In summary, the method for preparing the perovskite film provided by the present invention can passivate the surface defects of the perovskite film from multiple directions. Its application in perovskite solar cells can improve the photoelectric conversion efficiency and stability of the perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell prepared in Example 1 of the present invention;
[0027] Figure 2 This is a schematic diagram of the structure of a perovskite solar cell prepared in Example 3 of the present invention;
[0028] Figure 3 The current density-voltage (JV) curves of the perovskite solar cell devices prepared in Examples 1 to 6 of the present invention;
[0029] Figure 4 The functional conversion efficiency (PCE) of the perovskite solar cell device prepared in Examples 1 to 6 of the present invention varies with storage time;
[0030] Figure 5 The XRD patterns of pure lead iodide solution and lead iodide solution with guanyl phosphate urea molecules added.
[0031] Legend:
[0032] 1-transparent electrode; 2-hole transport layer; 3-light absorption layer; 31-lower interface passivation layer; 32-perovskite layer; 33-upper interface passivation layer; 4-electron transport layer; 5-metal electrode. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with specific embodiments.
[0034] Example 1: Preparation of perovskite solar cells
[0035] See also Figure 1 The structure of the perovskite solar cell prepared in this embodiment includes a transparent electrode 1, a hole transport layer 2, a light absorption layer 3, an electron transport layer 4 and a metal electrode 5 which are stacked in sequence from bottom to top.
[0036] The transparent electrode 1 (anode) is ITO conductive glass.
[0037] The hole transport layer 2 is a spin-coated 4PADCB ethanol solution, the 4PADCB ethanol solution is an anhydrous ethanol solution containing 4PADCB, the concentration of the 4PADCB in the 4PADCBz solution is 0.5 mg / ml, and the 4PADCB is 4-(7H-dibenzo[c,g]carbazole-7-yl)butylphosphonic acid.
[0038] The light absorbing layer 3 is an ABX3 type perovskite layer, wherein A includes cesium (Cs), methylamine (MA), and formamidinium (FA), B includes lead (Pb) and rubidium (Rb), and X includes bromine (Br) and iodine (I).
[0039] The electron transport layer 4 is a spin-coated PCBM chlorobenzene solution, the PCBM chlorobenzene solution is a chlorobenzene solution containing PCBM, the concentration of the PCBM in the PCBM chlorobenzene solution is 20 mg / mL, and the PCBM is [6,6]-phenyl C61 butyric acid methyl ester.
[0040] The metal electrode 5 (cathode) is Ag.
[0041] The preparation method is as follows:
[0042] (1) Cleaning of the transparent conductive glass substrate: Clean the ITO conductive glass in a UV ozone cleaning machine for 15 minutes according to the conventional method in the art to remove impurities on the substrate surface and improve the substrate wettability;
[0043] (2) Depositing a hole transport layer on a conductive glass substrate: Take 90 μL of 4PADCB ethanol solution and spin coat it on the conductive substrate at a speed of 3000 rpm for 30 seconds. Place the spin-coated film on a hot plate at 100°C for thermal annealing for 10 minutes to obtain a hole transport layer;
[0044] (3) Depositing a perovskite light absorbing layer on the hole transport layer: 8.4 mg of methylammonium bromide (MABr), 15.9 mg of rubidium iodide (RbI), 19.5 mg of cesium iodide (CsI), 27.5 mg of bromine iodide (PbBr2), 219.5 mg of formamidine hydroiodide (FAI), and 656.9 mg of lead iodide (PbI2) were dissolved in 800 μL of DMF and 200 μL of A perovskite precursor liquid was prepared in a mixed solvent of DMSO; 50 μL of the perovskite precursor liquid was taken and spin-coated on the hole transport layer by a two-step spin coating method, and the spin coating parameters were 1000 rpm for 10 seconds and 3000 rpm for 40 seconds; 100 μL of anisole was added as an anti-solvent 15 seconds before the spin coating, and finally the spin-coated film was placed on a hot stage at 100°C for thermal annealing for 10 minutes to obtain a perovskite light absorption layer;
[0045] (4) Depositing an electron transport layer on the perovskite light absorption layer: taking 70 μL of PCBM chlorobenzene solution, spin coating it on the perovskite light absorption layer at a speed of 1500 rpm for 30 seconds to obtain an electron transport layer;
[0046] (5) Depositing a buffer layer on the electron transport layer: taking 70 μL of a 0.5 mg / ml bromocresol purple sodium salt (BCP)-isopropanol solution, spin coating it on the electron transport layer at a speed of 5000 rpm for 30 s to obtain a buffer layer;
[0047] (6) When the vacuum degree is lower than 7.5×10-5Pa, 120nm thick silver (Ag) is evaporated on the buffer layer as the top electrode;
[0048] (7) The prepared device was placed in a desiccator overnight and then the JV curve was measured.
[0049] Example 2: Preparation of perovskite solar cells
[0050] The same as Example 1, except that 2 mg of guanyl phosphate urea (GAPh) is added to the perovskite precursor liquid used in depositing the perovskite light absorbing layer, that is, 8.4 mg of methylammonium bromide (MABr), 15.9 mg of rubidium iodide (RbI), 19.5 mg of cesium iodide (CsI), 27.5 mg of bromine iodide (PbBr2), 219.5 mg of formamidine hydroiodide (FAI), 656.9 mg of lead iodide (PbI2) and 2 mg of guanyl phosphate urea (GAPh) are dissolved in a mixed solvent of 800 μL DMF and 200 μL DMSO to prepare a perovskite precursor liquid.
[0051] Example 3: Preparation of perovskite solar cells
[0052] The same as Example 2, except that the light absorption layer includes a perovskite layer 32 and a lower interface passivation layer 31 and an upper interface passivation layer 33 disposed on the surface of the perovskite layer 32. The detailed steps of the preparation method are as follows:
[0053] (1) Cleaning of the transparent conductive glass substrate: Clean the ITO conductive glass in a UV ozone cleaning machine for 15 minutes according to the conventional method in the art to remove impurities on the substrate surface and improve the substrate wettability;
[0054] (2) Depositing a hole transport layer on a conductive glass substrate: Take 90 μL of 4PADCB ethanol solution and spin coat it on the conductive substrate at a speed of 3000 rpm for 30 seconds. Place the spin-coated film on a hot plate at 100°C for thermal annealing for 10 minutes to obtain a hole transport layer;
[0055] (3) Depositing a lower interface passivation layer on the hole transport layer: Take 90 μL of an IPA solution containing 0.4 wt% Al2O3, spin-coat it on the hole transport layer at a speed of 5000 rpm for 30 seconds, and place the spin-coated film on a hot plate at 100°C for thermal annealing for 10 minutes to obtain a lower interface passivation layer;
[0056] (4) Depositing a perovskite layer on the lower interface passivation layer: 50 μL of the perovskite precursor solution (Example 2) was taken and spin-coated on the lower interface passivation layer by a two-step spin coating method. The spin coating parameters were 1000 rpm for 10 s and 3000 rpm for 40 s. 100 μL of anisole was added as an anti-solvent 15 s before the spin coating. Finally, the spin-coated film was placed on a hot plate at 100° C. for thermal annealing for 10 min to obtain a perovskite layer Rb 0.05 Cs 0.05 MA 0.05 FA 0.85 Pb(I 0.95 Br 0.05 )3;
[0057] (5) Depositing an upper interface passivation layer on the perovskite layer: Take 50 μL of an IPA solution containing 1.5 mg / ml PEAI, spin-coat it on the perovskite light absorption layer at a speed of 5000 rpm for 30 seconds, and place the spin-coated film on a hot plate at 100°C for thermal annealing for 10 minutes to obtain an upper interface passivation layer;
[0058] (6) Depositing an electron transport layer on the upper interface passivation layer: taking 70 μL of PCBM chlorobenzene solution, spin coating it on the upper interface passivation layer at a speed of 1500 rpm for 30 s to obtain an electron transport layer;
[0059] (7) Depositing a buffer layer on the electron transport layer: taking 70 μL of a 0.5 mg / ml bromocresol purple sodium salt (BCP)-isopropanol solution, spin coating it on the electron transport layer at a speed of 5000 rpm for 30 s to obtain a buffer layer;
[0060] (8) When the vacuum degree is lower than 7.5×10-5Pa, 120nm thick silver (Ag) is evaporated on the buffer layer as the top electrode;
[0061] (9) The prepared device was placed in a desiccator overnight and then the JV curve was measured.
[0062] Example 4: Preparation of perovskite solar cells
[0063] The same as Example 2, except that 1 mg of guanidine chloride is added to the perovskite precursor liquid used in depositing the perovskite light absorbing layer, that is, 8.4 mg of methylammonium bromide (MABr), 15.9 mg of rubidium iodide (RbI), 19.5 mg of cesium iodide (CsI), 27.5 mg of bromine iodide (PbBr2), 219.5 mg of formamidine hydroiodide (FAI), 656.9 mg of lead iodide (PbI2) and 1 mg of guanidine chloride are dissolved in a mixed solvent of 800 μL DMF and 200 μL DMSO to prepare a perovskite precursor liquid for use.
[0064] Example 5: Preparation of perovskite solar cells
[0065] The same as Example 2, except that 1 mg of tricresyl phosphate is added to the perovskite precursor liquid used in depositing the perovskite light absorbing layer, that is, 8.4 mg of methylammonium bromide (MABr), 15.9 mg of rubidium iodide (RbI), 19.5 mg of cesium iodide (CsI), 27.5 mg of bromine iodide (PbBr2), 219.5 mg of formamidine hydroiodide (FAI), 656.9 mg of lead iodide (PbI2) and 1 mg of tricresyl phosphate are dissolved in a mixed solvent of 800 μL DMF and 200 μL DMSO to prepare a perovskite precursor liquid for use.
[0066] Example 6: Preparation of perovskite solar cells
[0067] The same as Example 2, except that 1 mg of guanidine chloride and 1 mg of tricresyl phosphate are added to the perovskite precursor liquid used in depositing the perovskite light absorbing layer, that is, 8.4 mg of methylammonium bromide (MABr), 15.9 mg of rubidium iodide (RbI), 19.5 mg of cesium iodide (CsI), 27.5 mg of bromine iodide (PbBr2), 219.5 mg of formamidine hydroiodide (FAI), 656.9 mg of lead iodide (PbI2), 1 mg of guanidine chloride and 1 mg of tricresyl phosphate are dissolved in a mixed solvent of 800 μL DMF and 200 μL DMSO to prepare a perovskite precursor liquid for use.
[0068] Figure 3 The current density-voltage (JV) curves of the perovskite solar cell devices prepared in Examples 1 to 6 of the present invention are shown. The performance parameters of the perovskite solar cells prepared in Examples 1 to 6 of the present invention are shown in Table 1 below.
[0069] Table 1. Performance parameters of perovskite solar cells
[0070] <![CDATA[V OC (eV)]]> <![CDATA[J SC (mA cm -2 )]]> FF(%) PCE(%) Example 1 1.15 24.85 83.36 23.91 Example 2 1.17 25.32 83.54 24.74 Example 3 1.17 25.40 84.52 25.21 Example 4 1.16 24.90 83.93 24.29 Example 5 1.17 25.12 83.12 24.38 Example 6 1.17 25.33 82.89 24.56
[0071] By comparing the parameters, it was found that compared with Example 1 without adding GAPh, Examples 2 and 3 with adding GAPh improved the photovoltaic performance of PSCs to varying degrees, and the photoelectric performance of PSCs prepared in Example 2 was significantly better than that of PSCs prepared in Example 4 (adding guanidine chloride), Example 5 (adding tricresyl phosphate) and Example 6 (adding guanidine chloride and tricresyl phosphate). The perovskite solar cell prepared in Example 3 showed the best photoelectric performance parameters, with an open circuit voltage of 1.17 eV and a short circuit current density of 25.40 mA / cm 2 , the filling factor is 84.52%, and the photoelectric conversion efficiency is 25.21%.
[0072] The stability of the perovskite solar cells prepared in Examples 1 to 6 is analyzed below. The analysis method is: the devices prepared in each example are placed in a nitrogen glove box for long-term storage, and their functional conversion efficiency (PCE) is measured regularly. The test results are shown in Figure 4 As shown, after 2300 hours of long-term monitoring, the PCE of the device in Example 3 is still the same as the initial PCE, the PCE of the device made in Example 2 can maintain about 98% of the initial PCE, while the PCE of the devices made in Example 1 and Examples 4 to 6 can only be maintained below 95% of the initial PCE after storage for 2300 hours, and that of Example 1 is even below 90%, indicating that the stability of the devices prepared in Examples 2 and 3 of the present invention is greatly improved.
[0073] The reaction product of GAPh and lead iodide was analyzed by XRD diffractometer: Figure 5 After adding guanyl urea phosphate molecules (GAPh) to lead iodide, the XRD of the mixed product showed new diffraction peaks compared with pure lead iodide, indicating that GAPh and lead iodide reacted to form an intermediate phase.
[0074] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a perovskite film, characterized in that: The following steps are involved: Step 1, preparing a perovskite precursor solution; Step 2, adding guanyl phosphate urea to the perovskite precursor solution of step 1 to obtain a modified perovskite precursor solution; Step 3: Spin-coat the modified perovskite precursor solution in step 2 onto the substrate using a solution spin coating method to prepare a perovskite film.
2. The preparation method according to claim 1, characterized in that: The perovskite precursor solution is obtained by dissolving an ABX3 type perovskite material in an organic solvent, wherein A is at least one of Cs, MA, and FA, B is at least one of Pb and Rb, and X is at least one of Br and I.
3. The preparation method according to claim 2, characterized in that: The organic solvent is a mixed solvent of DMF and DMSO, the DMF is N,N-dimethylformamide, and the DMSO is dimethyl sulfoxide.
4. The preparation method according to claim 3, characterized in that: The volume ratio of DMF to DMSO in the organic solvent is 4:
1.
5. The preparation method according to claim 1, characterized in that: The amount of the guanyl phosphate urea added is 0.8-1.5 g per liter of the perovskite precursor solution.
6. The preparation method according to claim 1, characterized in that: The step 3 comprises: Step 3.1, using a two-step solution spin coating method to spin coat the modified perovskite precursor liquid in step 2 on the substrate to obtain a perovskite wet film, the process parameters of the two-step solution spin coating method are: the first step rotation speed is 1000 rpm, the spin coating time is 10 s; the second step rotation speed is 3000 rpm, the spin coating time is 40 s, and the anti-solvent anisole is added dropwise 15 seconds before the spin coating; Step 3.2, annealing the perovskite wet film obtained in step 3.1 to obtain a perovskite thin film, wherein the process parameters of the annealing treatment are: annealing temperature 100° C., annealing time 10 min.
7. The preparation method according to claim 6, characterized in that: The amount of the anti-solvent anisole added is 10% of the volume of the organic solvent.
8. Use of the perovskite film obtained by the preparation method according to any one of claims 1 to 7 in a perovskite solar cell.
9. The use according to claim 7, wherein the structure of the perovskite solar cell comprises a transparent electrode, a hole transport layer, a light absorption layer, an electron transport layer and a metal electrode stacked in sequence, characterized in that: The light absorbing layer comprises a perovskite thin film obtained by the preparation method according to any one of claims 1 to 7.
10. The use according to claim 9, characterized in that: The light absorption layer also includes an upper interface passivation layer arranged on the upper surface of the perovskite film and a lower interface passivation layer on the lower surface, the passivation solution of the upper interface passivation layer is an IPA solution containing PEAI, the passivation solution of the lower interface passivation layer is an IPA solution containing Al2O3, the PEAI is phenylethylamine iodide, and the IPA solution is an isopropyl alcohol solution.
Citation Information
Patent Citations
Interface contact trans-perovskite solar cell module and preparation method and application thereof
CN113299833A
Cited By
Trans-perovskite solar cell and preparation method thereof
CN120787024A
Preparation method and application of perovskite thin film in perovskite solar cell
CN121358153A